The development of attacking and defending abilities during the transitional period of China's men's basketball team - Li, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The Chinese men`s basketball team is undergoing the shift from "short, swift and flexible" to "tall, swift, and flexible". The emergence of "three centre forwards" provides evidence of this transition. Further research is required to determine what changes have occurred, what problems the team has encountered, in the last ten years and what orientation the team will take. The paper proposes some suggestions for the men`s basketball team in their preparation for the 2008 Beijing Summer Olympic Games. The study also suggests strategies for the team`s future development based on such factors as players` change in height, performances in different periods, and top teams in the world. Methods: Methods included a review of the literature, video viewing and statistical analysis. Results Performances of the Chinese mens basketball team have improved to some extent in major matches along with the increase of the players` heights. The speed of attacking and defending, however is comparatively slow. The attacking points are 11.26 points less than the top four teams per round on average, especially in the 14th Championship event. Frontcourt rebounds, two-point shots, the abilities of breaching and confronting. Notably, the ability to finish the attack in confrontation, are delayed by comparison with the top teams in the world. However, an advantage was identified in three-point shots. With respect to height, the Chinese team stands 2.035 meters on average with the world`s top teams averaging 2.008 meters in height. This statistic confirms, the shift from "short" to "tall" in comaprison. However, there is still a long way to go in achieving the "swift" and "flexible" shift during performance. Conclusions The Chinese men`s basketball should coordinate the relationship between height and speed, and quicken the attacking and defending pace. The team should reform its training concepts, and aim to achieve competitiveness on the international stage not just at the Asian level. Team members should be encouraged to raise the awareness of attacking and confronting, especially when facing competition against the top world teams. The Chinese team has been endowed with top physical conditioning. A breakthrough can be achieved through scientific training in combination with particular tactics and strategies should be developed and implemented to confirm the link between tactics and morphological characteristics such as height and for the enhancement of an overall performance in the teams.